2017
DOI: 10.1149/2.0441709jes
|View full text |Cite
|
Sign up to set email alerts
|

Through-Mask Electrochemical Micromachining of Aluminum in Phosphoric Acid

Abstract: Aluminum micro-channels have been machined in phosphoric acid via mass-transfer limited electrochemical dissolution through photoresist masks. The results of shape evolution experiments using a rotating disk electrode are presented in terms of the dimensions, shape profile and uniformity of the machined micro-channels. The influences of applied potential, cumulative passed charge and hydrodynamic conditions on the shape evolution process are discussed. Experimental results are compared with a shape evolution m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The mass transport mechanism was obtained by potentiodynamic polarization experiments, which were carried out using a Princeton 2263 potentiostat controlled with PowerSuite software. Then the polarizations in ILs with a mixture of various concentrations (10,20,50 vol. %) of benzene were conducted to further confirm the rate limiting species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass transport mechanism was obtained by potentiodynamic polarization experiments, which were carried out using a Princeton 2263 potentiostat controlled with PowerSuite software. Then the polarizations in ILs with a mixture of various concentrations (10,20,50 vol. %) of benzene were conducted to further confirm the rate limiting species.…”
Section: Methodsmentioning
confidence: 99%
“…9 The salt precipitation mechanism describes a thin salt film present on the anode, where the surface concentration of metal cations equals to the saturation value at limiting current. 10 The acceptor mechanism looks at the role of adsorbed metallic species and the transport of the acceptor which solubilizes them. 11 The water mechanism involves the rate limiting diffusion of water from the bulk to the anode where it is consumed by formation of hydrated metal ions.…”
mentioning
confidence: 99%
“…Machining often takes place via immersion etching; hence, current densities and etch rates are usually lower than in saline electrolytes (0.1-10 A cm −2 , 1-10 μm min −1 ). 7,60,91,160 A wide range of metals has been machined, namely aluminum, 135,136,161,162 chromium, 91 copper, 42,55 gold, 163 hafnium, 91 molybdenum, 91,164,165 niobium, 166 platinum, 167 tantalum, 166 titanium 168 and tungsten. 91,169 This list is complemented by several cobalt, 91,160 copper 91,161 and nickel alloys, 91 as well as a number of stainless steels.…”
Section: Metals and Electrolytesmentioning
confidence: 99%
“…Similar in fabricating micro pillar arrays, the effects of the current density on surface morphology of the micro pillar arrays were investigated by Sun et al [11]. Baldhoff et al reported that speci c voltage is the key to micro channel shape uniform during TMEMM on aluminum [12]. Furthermore, the e ciency of the electrolyte characteristics on the current density is mainly affected by the conductivity, passivation, and activation of the solution.…”
Section: Introductionmentioning
confidence: 98%